Pengaruh Etika, Kesadaran Wajib Pajak, Sanksi Pajak, Dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak (Studi Kasus Wajib Pajak Orang Pribadi Di Kulon Progo) - Zainnita Julia Qhoirunnisa; Martinus Budiantara (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
The aim of this study is to find out how ethics, tax awareness, tax sanctions, and the quality of tax services affect the level of individual tax compliance in Kulon Progo. Primary data comes from questionnaires given to individual taxpayers. Secondary data is collected from relevant previous research and from various Internet sources. The double linear regression method is used to analyze data in the SPSS program version 21. Research results show that ethics, tax awareness, and tax sanctions have a positive impact on the level of individual tax compliance in Kulon Progo, but do not affect the quality of the tax services provided.